1999
DOI: 10.1589/jpts.11.95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heel Height on the Foot in Unilateral Standing.

Abstract: The purpose of this investigation was to study the effect of elevating the heel during unilateral weight-bearing on structure of the foot, especially a "flat" foot, and on function of the foot in maintaining balance. We examined 16 healthy women, 21 to 23 years of age, who stood unilaterally on the right foot with the heel elevated 0, 5, 10, 15, 20, 25, 30, and 40 mm. We measured height of the medial longitudinal arch, rearfoot pronation (calf-to-calcaneus angle), displacement of center of pressure under the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
4

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
2
16
0
4
Order By: Relevance
“…However, this finding suggests that the effect occurring under the TT condition indicates an imbalanced posture during tiptoe strategy according to the wider area of occupation. Since static squatting could be equated to standing in terms of nonsupported vertical posture, our results are generally consistent with those of previous studies in which the tiptoe posture contributed to posture instability (Dionisio et al, 2006;Hof et al, 2005;Shimizu and Andrew, 1999).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, this finding suggests that the effect occurring under the TT condition indicates an imbalanced posture during tiptoe strategy according to the wider area of occupation. Since static squatting could be equated to standing in terms of nonsupported vertical posture, our results are generally consistent with those of previous studies in which the tiptoe posture contributed to posture instability (Dionisio et al, 2006;Hof et al, 2005;Shimizu and Andrew, 1999).…”
Section: Discussionsupporting
confidence: 91%
“…Behaviorally, once TT was achieved, the hip and head of the metatarsophalangeal joint angle increased as the heel lifted up and affected the angle between the feet, causing it to be more open. Under this condition, Shimizu and Andrew (1999) suggested that the change of body angle was closely related to segmental body linkage coordination, which occurred as a compensation of balance control; therefore, the center of gravity is maintained within the BOS.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…São descritos muitos fatores predisponentes do pé plano, como idade, sexo e tipo de calçado utilizado, além de seu uso ou não [17][18][19] . Já Shimizu et al 20 relatam que, dentre os fatores predisponentes para o pé cavo, o uso de calçado de salto alto leva ao aumento na altura do arco longitudinal medial devido à tensão gerada na fás-cia plantar pela hiperextensão dos dedos.…”
Section: Introductionunclassified